A Review of the Pyramidal Training Approach for Practitioners Working With Individuals With Disabilities. (July 2017) - Andzik, Natalie; Cannella-Malone, Helen Irene
Pyramidal training has been used for many years to expedite training for those who work with individuals with disabilities and utilizes an expert who provides training to a practitioner who then trains another practitioner to implement practices with clients. Fourteen articles were analyzed to investigate the viability of this training approach for practitioners of all types who support individuals with disabilities. Research does support the effectiveness of pyramidal training within the parameters with which it has been evaluated in this review. All Tier 1 participants made improvement; 83% of Tier 2 participants and 43% of individuals with disabilities showed improvement. Future researchers are encouraged to analyze not only the fidelity of the implementation of these practices but also the changes among the individuals with disabilities. To that end, progress monitoring is necessary to determine whether the implementation was the cause for the meaningful gains for the population being served.